2000
DOI: 10.1111/j.1473-4192.2000.tb00139.x
|View full text |Cite
|
Sign up to set email alerts
|

The functions ofI thinkin political discourse

Abstract: The expression I (don't) think has in recent years received a fair amount of attention from different viewpoints and in different linguistic frameworks. After a brief survey of the most important literature on the subject, this article examines the occurrence of I think in political discourse as compared with its use in informal conversation. On the basis of two samples of 100 instances each from casual conversations and radio political interviews, the expression is looked at from the points of view of syntax,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
19

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 20 publications
4
71
0
19
Order By: Relevance
“…Other researchers interested in intersubjective positioning have demonstrated the importance of attending to the nature of the proposition. Thus, for example, various writers on the phrase I think have demonstrated the need to attend to whether the proposition is a 'fact' (a claim about some observable, verifiable state of affairs in the experiential world ) or some type of 'opinion' (see, for example, Stubbs 1996or Simon-Vandenbergen 2000. They have shown that the meaning or rhetorical functionality of I think varies according to the nature of the proposition (i.e., 'fact' versus 'opinion') it modulates.…”
Section: The Monoglossicmentioning
confidence: 99%
“…Other researchers interested in intersubjective positioning have demonstrated the importance of attending to the nature of the proposition. Thus, for example, various writers on the phrase I think have demonstrated the need to attend to whether the proposition is a 'fact' (a claim about some observable, verifiable state of affairs in the experiential world ) or some type of 'opinion' (see, for example, Stubbs 1996or Simon-Vandenbergen 2000. They have shown that the meaning or rhetorical functionality of I think varies according to the nature of the proposition (i.e., 'fact' versus 'opinion') it modulates.…”
Section: The Monoglossicmentioning
confidence: 99%
“…This provides some evidence that the political leaders treated the second and third debates less as conversations and more as political speeches. In order to examine the communicative functions of initial I think in the prehead, head and tonic I manually examined all 254 tokens in context by (a) considering the surrounding co-text, (b) the presence of lexical items signalling obligation, necessity, desirability tentativeness and uncertainty, (c) the presence of non-junctural pauses, hesitation markers and filled pauses, and (d) whether or not the I think was commutable by modal expressions such as probable, see Boye andHarder (2007), Fetzer (2014), Kearns (2007), Kaltenböck (2009), Simon-Vandenbergen (2000, and Van Bogaert (2010) for further information on methods used to disambiguate different uses of I think.…”
Section: Discussion and Further Questionsmentioning
confidence: 99%
“…Prehead There were four uses of I think found in prehead position, two of which have been previously described by Simon-Vandenbergen (2000) in her investigation of I think in political interviews. The first use indicates the strength of the speakers' commitment to the proposition.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations